Original scientific article Employer’s Abuse of the Right to Labour Management - Sitnikov, A. A. (Sibirskoe ûridičeskoe obozrenie (Online), 2021)
Introduction. In the process of employees’ labor managemeint, it is possible that the employer uses formally legitimate powers to harm the employee, therefore the article is devoted to studying the problem of employer’s abuse of the right to manage labor. Purpose. Give a legal description of the employer’s abuse of the right to manage labor in the exercise of discretionary powers, determine the relationship between the category of abuse of the right and discrimination in labor relations, and determine the consequences of such abuse, if a gap is identified in the legal regulation of problematic relations between the employer and employees, propose a draft of norms supplementing the Labor Code of the Russian Federation, ensuring proper protection of the rights and legitimate interests of the employees. Methodology. In addition to general scientific methods (analysis, synthesis, analogy), private scientific methods were also used, such as formally legal, systemic and comparative legal. Results. The right to labor management consists of normative permissible powers, with the help of which the operational management of labor is carried out. The exercise of formally legitimate powers with the aim of harming an employee is an abuse of the employer's right to manage labor, so the employer’s unlawful motive is a constituent element of abuse of the right. Actions, the result of which is a violation of the rights of workers, are not an abuse: they should be attributed to discriminatory actions, since the exercise of the right cannot entail a violation of another right. It is concluded that the current legislation does not provide a mechanism to protect employees from abuse by the employer. An analysis of the norms of the Civil Code of the Russian Federation shows that abuse of law is a form of unfair behavior, the principle of good faith is a general legal principle, and the existence in the Labor Code of the Russian Federation of norms providing for special consequences of unfair behavior of the parties to labor relations would help in solving the identified problem. A draft of norms supplementing the Labor Code of the Russian Federation designed to ensure adequate protection of the interests of employees from abuse of rights by the employer is proposed. Conclusion. Both in the doctrine and in practice, there is a confusion of the concepts of employee discrimination and abuse of law by the employer. From the point of view of the theory of law, it is necessary to distinguish between these categories, and the legislation should contain adequate mechanisms to protect employees from abuse of law by the employer.